SOX7 is involved in polyphyllin D-induced G0/G1 cell cycle arrest through down-regulation of cyclin D1 - Zheng Bin; Wang Gang; Gao Wenbo; Wu Qiquan; Zhu Weizhi; Weng Guobin (Acta Pharmaceutica)
The incidence of mortality of prostate cancer (PCa) has been an uptrend in recent years. Our previous study showed that the sex-determining region Y-box 7 (SOX7) was low-expressed and served as a tumor suppressor in PCa cells. Here, we describe the effects of polyphyllin D (PD) on proliferation and cell cycle modifications of PCa cells, and whether SOX7 participates in this process. PC-3 cells were cultured in complete medium containing PD for 12, 24, and 48 h. MTT assay was used to investigate the cytotoxic effects of PD. Cell cycle progression was analyzed using propidium iodide (PI) staining, and protein levels were assayed by Western blot analysis. Our results showed low expression of SOX7 in PCa tissues/cells compared to their non-tumorous counterparts/RWPE-1 cells. Moreover, PD inhibited the proliferation of PC-3 cells in a dose- and time-dependent manner. PD induced G0/G1 cell cycle arrest, while co-treatment with short interfering RNA targeting SOX7 (siSOX7) had reversed this effect. PD downregulated SOX7, cyclin D1, cyclin-dependent kinase 4 (CDK4), and cyclin-dependent kinase 6 (CDK6) expressions in a dose-dependent manner, whereas co-treatment of siSOX7 and PD rescued the PD-inhibited cyclin D1 expression. However, no obvious changes were observed in CDK4 or CDK6 expression. These results indicate that SOX7 is involved in PD-induced PC-3 cell cycle arrest through down-regulation of cyclin D1.